Molecular biology in cellular pathology [ - Crocker, J.; Murray, Paul [ (Paul G.)] (John Wiley & Sons, 2003)
Molecular biology has had a major impact on the practice of pathology in recent years and this continues with the new approaches being developed in genomics and proteomics. Knowledge of the molecular organization of the cell has led to the development of powerful new techniques which bring greater accuracy and objectivity to the diagnosis, prognosis and management of many diseases, and to the study of pathological states. This book is a completely revised and updated version of the popular Molecular Biology in Histopathology, with added material covering the latest methodologies and now feature